USM RESEARCHER EXCELS AT I-PHEX 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 25 August 2016 Medical students who were feeling stressful and being depressed has led a lecturer from the Universiti Sains Malaysia (USM) School of Medical Sciences (PPSP), Dr. Muhammad Saiful Bahri Yusoff to conduct a study using 'The Medical Students Stress Source Questionnaires (MSSQ): A Valid Screening to Discover Sources of Stress of Medical Students'.